The Role of FKIP Students of Lambung Mangkurat University in The Teaching Assistance Program in Banjarmasin: A Study of Academic and Non-Academic Activities - Rahmat Nur; Cucu Widaty; Sigit Ruswinarsih; Muhammad Adhitya Hidayat Putra; Sumiati Sumiati; Defica Arfianti Saragih; Andri Noor Azumardi (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2025)
This study aimed to determine the roles of FKIP students at Lambung Mangkurat University in academic and non-academic activities within the Teaching Assistance Program in Banjarmasin City. The study employed a phenomenological method with a qualitative approach. The stages of this study included: 1. Informant identification, 2. Data collection, 3. Data analysis, and 4. Data validity. The results indicate that in the academic dimension, students are generally capable of designing and implementing learning in accordance with the pedagogical principles they have learned, although some challenges remain in mastering cross-disciplinary material and implementing comprehensive learning evaluations. Meanwhile, in the non-academic dimension, students demonstrate strong communication, collaboration, and leadership skills, particularly in establishing relationships with teachers and students and in managing extracurricular activities.